2017
DOI: 10.1103/physrevb.95.064415
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the thickness dependence of the magnetic phase transition temperature in thin FeRh films

Abstract: FeRh and its first-order phase transition can open new routes for magnetic hybrid materials and devices under the assumption that it can be exploited in ultra-thin-film structures. Motivated by experimental measurements showing an unexpected increase in the phase transition temperature with decreasing thickness of FeRh on top of MgO, we develop a computational model to investigate strain effects of FeRh in such magnetic structures. Our theoretical results show that the presence of the MgO interface results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…In magnetic systems the source of this frustration is the inability to fully resolve the Ruderman-Kittel-Kasuya-Yosida (RKKY) exchange coupling present in the system 15 . In the case of FeRh the inability to resolve all the exchange interactions within the region between the two magnetic phases may also contribute to this behavior 49 . It is likely that both factors contribute to the jammed behavior seen in the XMCD measurements in Fig.…”
Section: Stretching Exponent Behaviormentioning
confidence: 99%
“…In magnetic systems the source of this frustration is the inability to fully resolve the Ruderman-Kittel-Kasuya-Yosida (RKKY) exchange coupling present in the system 15 . In the case of FeRh the inability to resolve all the exchange interactions within the region between the two magnetic phases may also contribute to this behavior 49 . It is likely that both factors contribute to the jammed behavior seen in the XMCD measurements in Fig.…”
Section: Stretching Exponent Behaviormentioning
confidence: 99%
“…T jump is known to be tunable in a wide temperature range [16,41,42]. To quantify the exchangemodulation function of the Fe-Rh layer, we use [43] A iex ðTÞ A iex ð0Þ ¼ α tanh…”
Section: Grainmentioning
confidence: 99%
“…According to measurements of Fe-Rh thin films in Refs. [40,43], we use a typical value of ΔT ¼ 20 K. The scaling and offset parameters are computed from the requirement of the remaining exchange-coupling fraction r ex well below…”
Section: Grainmentioning
confidence: 99%
“…A large number of recent experimental and theoretical studies have shown that the order-disorder phase transition in magnetic ultra-thin films may differ significantly from that in the corresponding bulk systems [3,7,10]. In the general case, the phase transition temperature (Curie temperature for the ferromagnetic (FM) thin film and Néel temperature for the antiferromagnetic (AFM) thin film) of the ultrathin films is lower than that in the bulk and decreases when the thickness of the film reduces.…”
Section: Introductionmentioning
confidence: 99%
“…The free energy of the thin film is calculated as follows: with the experimental results given in [7] and [10].…”
Section: Introductionmentioning
confidence: 99%